Perceptions of Medical Malpractice Liability and Informed Consent Among Hospital Healthcare Workers: A Cross-Sectional Study - Alina Doina Tănase; Ștefania Dinu; Raluca-Mioara Cosoroabă; Adriana Pădure; Cristina Ioana Talpoș Niculescu (Healthcare, 2026)
Background and Objectives: Rising malpractice litigation and the strengthening of patient-rights legislation have changed the way hospital staff approach informed consent and legal risk. This study aimed to (i) assess the distribution of informed-consent knowledge, malpractice anxiety, and defensive practice across professional and departmental groups; (ii) identify independent predictors of high defensive practice; and (iii) evaluate experience-related moderation of the legal-literacy–anxiety association and predictor consistency across defensive-practice severity. Methods: We conducted a cross-sectional survey of 146 healthcare workers (physicians, nurses, midwives, and allied health professionals) from four departments of a tertiary academic hospital network, using a 46-item pilot-tested instrument measuring informed-consent knowledge (0–20), malpractice anxiety (0–100), and defensive-practice behaviors. Results: Physicians showed higher informed-consent knowledge than nurses (14.1 vs. 12.0 points, p < 0.001) but also higher malpractice anxiety (63.4 vs. 57.6, p = 0.015). High defensive practice was associated with a prior malpractice claim (adjusted odds ratio 3.24), surgical specialty (2.47), low consent literacy (2.21), physician role (2.10), and knowing a sued colleague (1.88). Anxiety was highest in emergency medicine; predictors also operated across ordered defensive-practice severity, and the legal-literacy–anxiety association was stronger at lower experience (interaction p = 0.023). Conclusions: Knowledge, anxiety, and defensive practice were unevenly distributed; defensive practice reflected professional context and direct or vicarious litigation exposure, while the legal-literacy–anxiety association varied with experience. Medico-legal education may therefore be best paired with structured consent procedures and experience-sensitive support; larger multi-center studies are needed.